Engineering properties and environmental impact assessment of green concrete prepared with PVC waste powder: A step towards sustainable approach. (December 2022) - Manjunatha, M.; Seth, Dinesh; KVGD, Balaji; A, Bharath
Abstract: The primary objective of this study is to offer a comparative picture to assess the potential environmental impact and to reduce the energy required for concrete preparation. For this investigation, concrete is prepared with industrial wastes like PVC waste powder (PWP) and ground granulated blast furnace slag (GGBS) vis-a-vis conventional concrete. This investigation mainly focuses on the experimental study and environmental impacts of green versus conventional concrete using the life cycle assessment (LCA) approach. LCA models are prepared for green concrete by considering industrial waste by-products materials like GGBS and PWP. For this study, green concrete is considered by using 30% constant GGBS for all the mixes. In contrast, PWP is considered in varying percentages like 0%, 5%, 10%, 15%, 20%, 25%, and 30% by weight of cement and compared with conventional concrete prepared. To compare the environmental impacts of green and conventional concrete, initially, authors compared the physical and chemical properties of materials, fresh and hardened properties of concrete for all the mixes. Based on test results, LCA models are prepared by using SimaPro software and the Ecoinvent database. The originality of this study lies in offering a comparative picture for researchers and practitioners. Experimental investigation of this study exhibits that concrete prepared with PWP (15–20%) and fixed contents of GGBS helps to improve the structural performance and durability properties of green concrete. This investigation also indicates that green concrete prepared with PWP and GGBS helps to reduce environmental damage substantially.